Potencial invasor de Syzigium jambos (Myrtaceae) en fragmentos boscosos: El caso de Ciudad Colón, Costa Rica - Di Stéfano, José Fco. (1998)
Syzigium jambos is a rnultiple use species native to Southeast Asia that has been introduced in rnany countries of the world. Similar to sorne other exotics, it has the potential to becorne naturalized and invade natural ecosysterns. In Costa Rica, it has been observed in several srnall preserves. A sample of 48 quadrats of 0.6 rn of radius, in one hectare fragrnent (with a 30 year-old secundary hurnid Prernontane forest) had a density of 4.9 seedlings and 0.16 saplings per rn2. Higher densities were observed near the base of the adult trees (N=3) and on the biggest of the trees investigated. Growth rates of the seedlings and saplings was very low: less than 10.5 and 0.25 crnlyear in height and basal diameter, respectively. In general, the plants had low levels «30%) of relative damage by herbivores, and fungi (one identified as a Puccinia psidii Wint.) on their leaves, although a significant increase was detected by the end of the wet season and beginning of the dry season. Srnall white epiphyllic liquens were abundant on rnature leaves. Apparently the species is very flexible as little rnechanical damage was observed.